Management of Degenerative Meniscus Injury: Surgical vs Conservative approach - Dawidowicz, Marcel; Kucharski, Kacper; Majda, Antoni; Aleksandrowicz, Hanna; Kamosińska, Anna; Laske, Alicja; Sowa, Martyna; Sitko, Natalia; Makowska, Paulina; Kowal, Adam; Gontarczyk, Joanna; Pająk, Julia (Journal of Education, Health and Sport, 2026)
Objective: This review aims to compare surgical and conservative treatment methods for degenerative meniscus injuries. Methods: A literature search was conducted in PubMed, Scopus, Web of Science, and the Cochrane Library to identify randomized controlled trials published from 2012 onwards. Eligible studies evaluated adult patients with degenerative meniscal tears confirmed by magnetic resonance imaging or radiographs, comparing surgical interventions with non-operative treatments. Results: Evidence from high-quality trials indicates that conservative approaches are comparable to surgical interventions in improving long-term patient-reported outcomes. While arthroscopic partial meniscectomy (APM) yields significant initial clinical improvements, it offers no meaningful long-term advantage over structured physical therapy. Placebo-controlled trials demonstrate that the perceived therapeutic benefits of APM are predominantly due to the non-specific effects of the surgical act itself rather than the removal of damaged tissue. Conversely, APM exposes the knee to accelerated degenerative changes, including an increased risk of radiographic osteoarthritis progression and a five-fold higher likelihood of ultimately requiring a total knee replacement. Furthermore, patients who crossover from physical therapy to delayed surgery due to unsatisfactory results do not achieve superior functional outcomes compared to those who remain in conservative management. Conclusion: Current clinical guidelines advocate for at least three months of structured physical therapy as the primary, first-line treatment for degenerative meniscal lesions. Adopting a conservative approach maximizes patient benefit, prioritizes the preservation of the meniscus, and supports long-term joint longevity.